Health related fitness performance: Comparison between Malaysian urban, rural, and aboriginal secondary school students / Nur Syahirah Abu Hasan - Abu Hasan, Nur Syahirah (Faculty of Sport Science and Recreation, 2016)
The purpose of this study was to compare health related fitness performances of body composition, flexibility, muscular endurance, muscular strength and cardiovascular endurance on urban, rural and aboriginal secondary school students. SMK Wangsa Maju Seksyen 2 represented urban, whereas SMK Felda Bukit Sagu represents rural area and SMK Kuala Krau representing aboriginal area. A total of three hundred students (N=300) were selected via stratified random sampling participated in this study. Results showed that there was a significance difference (p<O.05) in muscular strength, aboriginal (p=.OOI) and urban area (p=.OOI). In muscular endurance, rural area showed (p=.022) and aboriginal area showed (p=.OOl) which indicated significance difference of (p<O.05) and for cardiovascular endurance, urban area showed (p=.OOl) and aboriginal area showed (p=.005). There was no significance difference in body composition and flexibility (p>O.05). As conclusion, the findings in this study indicated that the difference in physical fitness performance among urban, rural and aboriginal secondary school students was influenced by different types of their daily activity involvement.